Carotenoids improve bacterial tolerance towards biobutanol through membrane stabilization. Issue 1 (6th January 2021) - Chia, Geraldine W. N.; Seviour, Thomas; Kjelleberg, Staffan; Hinks, Jamie
Abstract : The nano-aggregation of carotenoids in microbial membranes increases membrane stability upon butanol exposure by reducing the fluidization effect and membrane permeability of butanol. Abstract : Microbial butanol production is an important sustainable energy option, but it is economically limited by poor process performance. Butanol is toxic and damages bacterial cell membranes, requiring cells to expend energy for survival rather than for butanol production. Here we explore the utility of two polar carotenoids, lutein (LUT) and zeaxanthin (ZEA), as molecular rivets to mitigate membrane fluidization by solvents and thus improve butanol tolerance in Escherichia coli . LUT and ZEA formed carotenoid-rich nanodomains in multilamellar vesicles, at molar ratios of 1 : 9 relative to phospholipids (10 mol%), which reduced the fluidization effect of 3.5% (v/v) butanol by 62%, as indicated by changes in generalized polarization values of the membrane fluidity probe, Laurdan. Additionally, membrane penetration of butanol was 38% lower in the same test system. In carotenoid-treated E. coli, butanol-induced membrane damage, determined by propidium iodide, decreased by up to 30%. Additionally, E. coli treated with both LUT and ZEA achieved a two-log increase in cell viability upon acute butanol exposure of 3.5% (v/v), compared to untreated cells. This is the first time that carotenoids have been used to fortify cellular membranes and reduce biomass loss due to butanol, thereby revealing a potential biotechnological application for carotenoids to improve the economics of microbial butanol production.